Deflation versus maintained inflation of gastric band in pregnancy: A national cohort study. (June 2017) - Jefferys, Amanda; Lenguerrand, Erik; Cornthwaite, Katie; Johnson, Andrew; Lynch, Mary; Hyde, Judith; Draycott, Tim; Siassakos, Dimitrios
Background: With no evidence to guide management of the gastric band in pregnancy, we aim to compare outcomes according to band management. Methods: Data were collected on all women pregnant (November 2011–October 2012) following gastric banding, using the UK Obstetric Surveillance System surveillance system. We compared outcomes between band management groups and with national data. Results: Band management was variable; deflation 43.4%, inflation maintained 56.6%. The deflation group had lower risk of small for gestational age infants (no cases vs. 11.3%; risk ratio = 0.14, p  = 0.05). There was greater gestational weight gain (deflation 15.4 kg, inflation 7.6 kg; adjusted p  = 0.05), and perhaps higher risk of gestational hypertension (deflation 10.5%, inflation no cases; p  = 0.08) in the deflation group. Other maternal outcomes were similar between management groups but overall worse than national data. Conclusions: Deflation is associated with better outcomes for babies but worse outcomes for mothers than maintained inflation.